AB0337 Questionnaire Survey on 100 Chinese Physicians for Awareness of Hepatitis B Virus Infection in Rheumatoid Arthritis Patients. (10th June 2014) - Liang, A.-Q.; Mo, Y.-Q.; Zheng, D.-H.; Zhu, L.-J.; Dai, L.
Abstract : Background: Approximate 7.2% Chinese have been suffered from chronic hepatitis B virus (HBV) infection manifesting positive HBsAg. Our previous study showed the positive rate of HBsAg in Chinese rheumatoid arthritis (RA) patients was 11.3% (2013, Clin Rheumatol). Screening of HBV infection prior to immunosuppressive therapy, monitoring and antiviral prophylaxis during DMARDs treatment are recommended for HBsAg(+) RA patients by ACR 2008/2012 recommendations. However, little is known about the real-world clinical practice of Chinese physicians. Objectives: To investigate Chinese physicians' awareness of HBV infection in RA patients and to identify the important targets of education. Methods: A cross-section survey of 100 physicians who treated RA patients in daily clinic was conducted with a modified ACR questionnaire (2010, Arthritis Care & Research). The questionnaire was composed of demographic data and 10 questions concerning essential areas of screening HBV infection, monitoring and antiviral prophylaxis (or therapy) during immunosuppressive therapy for RA patients. Each question has 4-7 options for choice. The questionnaires with ≥8 answered items were regarded as valid for statistical analysis. Results: 1. 100 physicians were recruited for the survey and 92 questionnaires with ≥8 answered items were valid for statistical analysis. Among them, 73% were rheumatologist, 27% were non-rheumatologists including internal medicine physicians (14%), orthopedists (8%), traditional Chinese medical physicians (2%) and other specialists (3%). The mean working seniority was 11.3 years (range, 1-32) and 73% physicians were consulted more than 5 RA patients per month. 2. Twenty-three percentage of physicians reported no routine screening for HBV infection before immunosuppressive therapy for outpatients with RA, comparing 92% for hospitalized RA patients. During immunosuppressive therapy for HBsAg(+) RA patients, 36% physicians reported no regular monitoring of HBV DNA and 12% reported no regular monitoring of aminotransferases. Twenty-four percentage of physicians considered antiviral prophylaxis for HBsAg(+) RA patients and regarding to the detailed indications of antiviral prophylaxis, 62% (57/92) physicians considered high HBV load, 39% (36/92) considered elevated aminotransferases, and 32% (29/92) considered both HBsAg(+) and HBeAg(+). 3. Eighty-eight percentage of physicians had clinical experience of antiviral prophylaxis or therapy for RA patients. Among them, 62% prescribed antiviral drug before or at the initiation of immunosuppressive therapy and 38% prescribed antiviral drug after HBV reactivation. Conclusions: Our results showed that Chinese physicians have poor awareness of HBV infection for RA patients. The further CME should emphasize the routine screening for HBV infection especially in RA outpatients, regular monitoring of HBV DNA for HBsAg(+) RA patients, and antiviral prophylaxis considered to all HBsAg(+) RA patients with immunosuppressive treatment. Acknowledgements: This work was supported by Specialized Research Fund for the Doctoral Program of Higher Education (no.20130171110075) and Natural Science Foundation of Guangdong Province, China (no.S2013010014396) to L. Dai; Medical Scientific Research Foundation of Guangdong Province, China (no.A2013201) to Y-Q. Mo; Chinese National Natural Science Research Grant (Grant no. 81373183 and 81001334) to L-J. Zhu. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4022